Socialization Building Student Economic Literacy In Students Of Sma Pgri 4 Padang In The Era Of The Industrial Revolution 4.0 - Dessyta Gumanti; Reni Respita (Peneliti Teknologi Teknik Indonesia, 2021)
The purpose of the activity is to socialize economic literacy for students in facing the era of the industrial revolution 4.0 in the rest of SMA PGRI 4 Padang, so that students can make smart decisions regarding the various options available, especially in economic activities in everyday life. Direct observation, interviews, and questions and answers are used to execute socialization to increase economic literacy, as well as socialization through lectures/information, training, and simulations. The results of these activities include: providing knowledge to participants about the application of economic literacy in making economic decisions in everyday life.